Inteligencia emocional y resiliencia en mujeres ingresadas en el centro de Privación de Libertad para personas adultas Mixto Loja, de la ciudad de Loja - Castillo Guaylupo, María Cecibel (2020)
Currently, the penitentiary system in our country is under going circumstances that have caused a state of crisis, there fore, all researches focused on improving the quality of life of people deprived of liberty are considered relevant. This study is important, as it investigates relevant aspects of clinical psychology,and it is necessary to considerthe issues related to Emotional Intelligence and Resilience in persons deprived of liberty inthe Loja detention center for adults.Thegeneral objectiveof this research isto determine the relationship between emotional intelligence and resilience of women admittedinto the Loja Detention Center for menand women.For thispurpose, information was collected from 75 women deprived of liberty. This was a relational study with a cross section and a quantitative approach.The Automated Bar-On I-CE Emotional Inventory and the Wagnild & Young Resilience Scale were used as data collection instruments. There sultsshowed a relationship between emotional intelligence and resilience, with statistically significant data, evidencing that, faced with a lower emotional quotient, women deprived of liberty at the Detention Center for Adult Men and Women, will show low resilience level. Finally, it is recommended to apply the plan for mental health promotion and prevention, which was proposed in order to provide tools that promote better mental health in people deprived of liberty. Key words: deprived of liberty, Emotional intelligence, resilience.